Comparison of effects of aspirin and indomethacin on human platelet prostaglandin synthetase. Issue 5 (October 1977) - Crook, D; Collins, A J
Abstract : Human platelets were incubated in vitro with either aspirin or indomethacin and the prostaglandin synthetase activity of the resultant microsomal fraction from each incubation measured using a radiometric technique. Whereas aspirin produced a dose-related inhibition of the enzyme, indomethacin produced little or no inhibition over the same concentration range (10(-6) mol/l--10(-3) mol/l). Furthermore, administration of aspirin (600 mg) to volunteers produced a highly significant, prolonged inhibition of platelet microsomal prostaglandin synthetase whereas no inhibition was found with indomethacin (50 mg). As indomethacin is considerably more potent than aspirin as an inhibitor of human platelet prostaglandin synthetase in vitro, the results suggest a fundamental difference in the nature of the inhibition produced by each drug, aspirin being an essentially irreversible inhibitor whereas the inhibition produced by indomethacin is reversible. Studies with [3H-acetyl] aspirin have confirmed previous findings (Roth and Majerus, 1975) that aspirin produces an irreversible acetylation of a particulate fraction protein from human platelets.